1988
DOI: 10.1002/jsfa.2740440304
|View full text |Cite
|
Sign up to set email alerts
|

Determination of endogenous amino acid flow at the terminal ileum of the rat

Abstract: A B S T R A C TIn a comparative study endogenous amino acid jlow was determined in twenty-four 190-g male rats (protein-replete) given diets containing synthetic amino acids as the sole nitrogen source but devoid of specific amino acids, and six rats fed a protein-free diet. Endogenous flows were not significantly different ( P > 0.05) for aspartic acid, glutamic acid, serine and lysine but were significantly higher ( P < 0.05) under protein free alimentation than amino acid alimentation for proline, glycine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

1990
1990
2006
2006

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 11 publications
1
12
1
Order By: Relevance
“…The value for lysine flow at the terminal ileum of rats given a protein-free diet in the present study was considerably lower than a comparable value (400 pg g-' dietary dry matter) reported by Bolton and Miller (1985). Conversely, however, the present values for ileal lysine and amino acid flows for the protein-free-fed rats were higher than comparable values found by Skilton et a1 (1988) andDarragh et a1 (1990). This was also the case for flows determined after feeding the rats an EHC-based diet.…”
Section: Discussioncontrasting
confidence: 74%
“…The value for lysine flow at the terminal ileum of rats given a protein-free diet in the present study was considerably lower than a comparable value (400 pg g-' dietary dry matter) reported by Bolton and Miller (1985). Conversely, however, the present values for ileal lysine and amino acid flows for the protein-free-fed rats were higher than comparable values found by Skilton et a1 (1988) andDarragh et a1 (1990). This was also the case for flows determined after feeding the rats an EHC-based diet.…”
Section: Discussioncontrasting
confidence: 74%
“…The ultrafiltrate N comprised mostly peptides and free amino acids, with minor contributions from urea, ammonium and creatinine. The endogenous ileal amino acid and nitrogen flows for the growing rat determined in the present study were lower than those reported by Taverner (1979) and Bolton and Miller (1985), but similar to those found by Skilton et al (1988), Darragh et a1 (1990), Moughan and Rutherfurd (1990) and Butts et ul(1991).…”
supporting
confidence: 47%
“…13,15,18 The high level of proline is thought to be due to the breakdown of muscle protein to supply the amino acids required for metabolism. 19 There is also evidence that the ef®cient absorption of proline is dependent on an adequate supply of protein in the diet.…”
Section: ±15mentioning
confidence: 99%